2022
DOI: 10.3390/jcm11206177
|View full text |Cite
|
Sign up to set email alerts
|

Implication of COVID-19 Pandemic on Adolescent Mental Health: An Analysis of the Psychiatric Counseling from the Emergency Room of an Italian University Hospital in the Years 2019–2021

Abstract: Introduction: Although the COVID-19 pandemic had profound consequences on youths’ mental health, few data are available about its longitudinal implications. Method: In this study, from 655 counseling requests by the Emergency Room (ER) of the University Hospital of Bari, we retrospectively examined 380 requests for psychiatric counseling of pediatric subjects, during the pre-pandemic, the first pandemic, and the second pandemic wave of COVID-19. Results: We found a significant upward trend between 2019 and 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
(57 reference statements)
4
12
0
Order By: Relevance
“…After calculation, it was found that only 1.6% (7/436) adolescents in our present study reported a positivity ratio of ≥2.9, suggesting that the vast majority (98.4%) adolescents were living a not flourishing life in this special time. This low positive ratio is not surprising and is consistent with recent studies showing that the COVID-19 pandemic severely disrupted the wellbeing and mental health of youths (Wang et al, 2021;Bui et al, 2022;Petruzzelli et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…After calculation, it was found that only 1.6% (7/436) adolescents in our present study reported a positivity ratio of ≥2.9, suggesting that the vast majority (98.4%) adolescents were living a not flourishing life in this special time. This low positive ratio is not surprising and is consistent with recent studies showing that the COVID-19 pandemic severely disrupted the wellbeing and mental health of youths (Wang et al, 2021;Bui et al, 2022;Petruzzelli et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…They have also reported that the incidence rate increase was higher among females and increased faster in mid-adolescence patients. Worryingly, during the three years of the COVID-19 pandemic (2019–2021), the number of suicide attempts by children and adolescents up to 18 years of age increased [ 37 ] along with an upward longitudinal trend of acute psychopathological symptoms, including depression, post-traumatic-stress disorder, and psychosis [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased psychological stress during the pandemic was associated with an increased risk of active suicidal ideation and its severity [ 9 ]. Longitudinally, the pandemic influenced the type and complexity of mental health problems, increasing the diversity and severity of suicidal behaviors and the frequency of counseling for psychotic symptoms [ 10 ]. The presence of passive suicidal ideation has been recently reported in 10.5% of 9-year-old children [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Petruzzelli and colleagues [ 17 ] highlighted a significant increase in psychiatric counseling in the Emergency Room in 2020–2022 compared to 2019, particularly for acute psychopathological symptoms in adolescent patients.…”
Section: Introductionmentioning
confidence: 99%